2011
DOI: 10.1097/aud.0b013e3182251a0e
|View full text |Cite
|
Sign up to set email alerts
|

The Placebo Effect and the Influence of Participant Expectation on Hearing Aid Trials

Abstract: These results suggest a need to control for placebo effects in hearing aid trials and to interpret cautiously any hearing aid trial that did not control for this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 33 publications
5
39
2
Order By: Relevance
“…The results' pattern observed in those two placebo studies (i.e. small effects on behavioural speech recognition measures along with greater effects on subjective benefit, sound quality or preference ratings) was very similar to past unblinded HA comparison study results [40], and also to our present results.…”
Section: Discussionsupporting
confidence: 78%
“…The results' pattern observed in those two placebo studies (i.e. small effects on behavioural speech recognition measures along with greater effects on subjective benefit, sound quality or preference ratings) was very similar to past unblinded HA comparison study results [40], and also to our present results.…”
Section: Discussionsupporting
confidence: 78%
“…In a subsequent replication of this study (Dawes et al 2013), the results were repeated, and this time with a clearly significant effect of labeling on speechin-noise performance. The studies by McClymont et al (1991), Bentler et al (2003), and Dawes et al (2011Dawes et al ( , 2013 were all concerned with procedural pitfalls for research and clinical studies rather than clinical practice, but their results can also be considered as forms of narrative effect; the narrative provided by the experimenter influenced the treatment outcome independently of the treatment content.…”
Section: Introductionmentioning
confidence: 99%
“…No labeling effect was found in the behavioral outcome measures. Dawes et al (2011) aimed to examine possible placebo effects (defined as clinical responses associated with expectation rather than with any intrinsic property of the treatment) in HA clinical trials. Subjects underwent a crossover design comparing two HA fittings in a single laboratory session.…”
Section: Introductionmentioning
confidence: 99%
“…Bentler et al concluded that the participants ' expectation that ' digital ' hearing aids must be better had affected both performance of measures of hearing-aid benefi t and their overall preference. Dawes et al (2011) went on to investigate the impact of patient expectation on the outcome of a trial of two hearing aids. The aim of Dawes et al ' s study was to test whether the effect of expectation observed by Bentler and colleagues was specifi c to the ' digital ' label, or whether a more general label of ' new technology ' could set up positive expectations about performance, with a consequent impact on outcome measures.…”
mentioning
confidence: 99%